Evaluating pelvis rotation style at foot contact: A propensity scored biomechanical analysis in high school and professional pitchers - Manzi, J. E.; Zeitlin, J. H. Dowling, B.; Roberts, N.; Ruzbarsky, J. J.; Ciccotti, M. C.; Dines, J. S. (The American Journal of Sports Medicine, 2022)
Background: Early pelvis rotation has been associated with decreased throwing arm kinetics and conventionally was considered a component of proper pitching form in baseball throwers. However, previous assessments of pelvis rotation style have not accounted for confounders such as playing level, anthropometric characteristics, or ball velocity and have not evaluated sufficient sample sizes.